Application of MPA to estimate probability of collapse of structures. - Han, Sang Whan (Earthquake engineering & structural dynamics.)
This paper develops a modal pushover analysis- (MPA) based approximate procedure to quantify the collapse potential of structural systems. The computationally demanding incremental dynamic analysis (IDA) of the structural system is avoided by MPA of the structure in conjunction with empirical equations for the collapse strength ratio for the first-mode single-degree-of-freedom (SDF) system; higher modes of vibration play essentially no role in estimating the ground motion intensity required to cause collapse of the structure. Presented are collapse fragility curves for 6-, 9-, and 20-story regular special moment-resisting teel frames computed by the exact and approximate procedures, demonstrating that the MPA-based approximate procedure requires only a small fraction (1% in one example) of the computational effort inherent in exact IDA and still achieves highly accurate results.